FEATURES OF THE UNIFIED FINNISH EDUCATION SYSTEM IN UZBEKISTAN - Turumbetova Aygul Yusupbaevna (American Journals, 2023)
This article describes the unique features and implications of implementing the Unified Finnish Education System in the educational context of Uzbekistan. The article examines the adoption of Finnish educational principles and methodologies, considering the cultural, social, and structural factors influencing the adaptation and effectiveness of the system in Uzbekistani schools. The research provides insights into policy transfer dynamics, the cultural adaptation of educational practices, and the impact on various aspects of the Uzbekistani education system. The author assumes that while acknowledging the unique cultural and structural differences, the incorporation of these features might contribute to the ongoing educational reforms in the Republic of Uzbekistan, promoting a more holistic and student-centered approach to learning.
Keywords: Features, implications, implementing, the Unified Finnish Education, System, Uzbekistan, educational practices.